2018
DOI: 10.1111/jvim.15227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an extruded animal protein‐free diet on fecal microbiota of dogs with food‐responsive enteropathy

Abstract: BackgroundDietary interventions are thought to modify gut microbial communities in healthy individuals. In dogs with chronic enteropathies, resolution of dysbiosis, along with remission of clinical signs, is expected with treatment.Hypothesis/ObjectiveTo evaluate changes in the fecal microbiota in dogs with food‐responsive chronic enteropathy (FRE) and in healthy control (HC) dogs before and after an elimination dietary trial with an animal protein‐free diet (APFD).AnimalsDogs with FRE (n = 10) and HC (n = 14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
6
37
1
1
Order By: Relevance
“…However, for dogs, the kingdom of origin of the ingredients seems to be less important than the overall macronutrient composition. Extruded diets with similar macronutrient contents, but prepared exclusively with vegetable sources of protein, do not seem to significantly alter the microbiome of dogs when compared to traditional (mixed animal and vegetable) extruded diets (22).…”
Section: The Effect Of Dietmentioning
confidence: 88%
See 1 more Smart Citation
“…However, for dogs, the kingdom of origin of the ingredients seems to be less important than the overall macronutrient composition. Extruded diets with similar macronutrient contents, but prepared exclusively with vegetable sources of protein, do not seem to significantly alter the microbiome of dogs when compared to traditional (mixed animal and vegetable) extruded diets (22).…”
Section: The Effect Of Dietmentioning
confidence: 88%
“…Dogs with FRD had a decrease of Enterococcus spp., Corynebacterium spp., and Proteobacteria, all potential pathogens, in the duodenum after treatment. In another study focusing on dogs with FRD (22), after an elimination dietary trial with a vegetable protein diet, the microbiome diversity was no longer significantly different from healthy controls, and richness was significantly increased.…”
Section: Gut Microbiome and Gi Diseasesmentioning
confidence: 95%
“…Studies investigating the direct impact of protein on gut microbiota composition and functionality have shown that protein quality and source are as important as total amounts in people, but less so in dogs [2, 16,44]. Analysis of the gut microbiota showed that diet C (all-meat/high protein diet) in our study was characterised by an overrepresentation of bacteria belonging to the Fusobacteria phylum.…”
Section: Discussionmentioning
confidence: 57%
“…Similar studies have been performed regarding the effect of fibre on the gut microbiota of dogs [5][6][7][8][9][10][11][12][13][14][15]. Some studies have shown beneficial effects and changes in the gut microbiota [5,15], whereas others have not shown any significant change [6,12,14,16,17]. Results have been dependent on the type of fibre, percentage of fibre, previous diet fed, duration of treatment, health status and methodology used during the analysis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation